Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fphys.2019.00317
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Responses to a Lifestyle Intervention Do Not Account for Inter-Individual Variability in Glucose Tolerance for Individuals at High Risk of Type 2 Diabetes

Abstract: Background: Lifestyle interventions have been shown to delay or prevent the onset of type 2 diabetes among high risk adults. A better understanding of the variability in physiological responses would support the matching of individuals with the best type of intervention in future prevention programmes, in order to optimize risk reduction. The purpose of this study was to determine if phenotypic characteristics at baseline or following a 12 weeks lifestyle intervention could explain the inter-individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Another challenge for countermeasure design and implementation is the individual variation in response to lifestyle interventions (Bouchard and Rankinen, 2001;Solomon, 2018;O'Donoghue et al, 2019). While a specific exercise program may, on average, be effective there can be a broad range in the individual response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another challenge for countermeasure design and implementation is the individual variation in response to lifestyle interventions (Bouchard and Rankinen, 2001;Solomon, 2018;O'Donoghue et al, 2019). While a specific exercise program may, on average, be effective there can be a broad range in the individual response.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the improvement in insulin sensitivity was greater in the CTRL group than in the JUMP group. It has previously been highlighted that there is substantial inter-individual variability in physiological responses following lifestyle interventions (Bouchard and Rankinen, 2001;Solomon, 2018;O'Donoghue et al, 2019). In addition, the genes and pathways underlying the response to exercise training and physical inactivity differ (Booth et al, 2012;Pillon et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22] We cannot assume outcomes of earlier trials (in different high risk glycemic populations with IGT), are simply translatable to populations with current high risk intermediate glycemic categories , who differ in pathophysiology, progression rates, and vascular risk. [24][25][26][27] The diabetes prevention benefit found in the earlier high intensity landmark trials [19][20][21][22] has been much less marked in 'real world' pragmatic interventions. 28,29 This means that although there is a need for lower cost, more pragmatic intervention models, the current evidence to support their effectiveness is limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all findings are consistent with the aforementioned results. Recent findings wherein 285 participants aged 18-75 years participated in a 12-week lifestyle intervention including both dietary and exercise guidance suggested that those who experienced greater improvement in glucose tolerance presented with higher baseline weight, visceral fat, fasting glucose, and triglyceride concentration compared to those who did not respond (9). Thus, it is unclear whether and how baseline phenotypes influence insulin sensitivity responses to diet and exercise-induced weight loss, and response likely depends on multiple factors.…”
Section: Introductionmentioning
confidence: 99%